(untitled) (London Journal of Research In Management & Business, 2025)
Today’s healthcare administrators are not just managers; they are innovators operating within a dynamic and creative environment. Their approaches elevate the healthcare management sector and significantly contribute to social security by acting as vital knowledge partners in transformational initiatives. The training programs are designed as an effective blend of academic rigor and industry-relevant insights, providing a critical understanding of corporate culture and amplifying the importance of healthcare managers in the evolving job market. In response to the rapidly changing landscape, new skill sets identified include communication, collaboration, change management, team leadership, motivation, analytical thinking, and logical reasoning, have emerged that emphasize the need for ongoing learning, unlearning, and relearning. The curriculum is shaped by comprehensive competency mapping, ensuring alignment with the demands of modern healthcare.